The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/ijc.2910380605
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to HTLV‐I in Nigerian blood‐donors, their relatives and patients with leukaemias, lymphomas and other diseases

Abstract: Antibodies to HTLV-I have been detected in sera from 15 (2.0%) of 736 adult blood-donors in Nigeria, in 4 (20.0%) of 20 patients with chronic lymphatic leukaemia, 3 (10.0%) of 30 with non-Hodgkin's lymphoma, one of 12 with Burkitt's lymphoma and one of 7 with acute lymphoblastic leukaemia. The frequency of positivity was higher (3.6%) in the blood-donors from the guinea and wooded savanna of northern Nigeria than in those from the rain-forest and mangrove swamps of southern Nigeria (1.8% in Lagos and 0.7% in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 38 publications
2
28
1
1
Order By: Relevance
“…The clinical features of ATL in Nigeria differed from those described in other endemic areas. For example, the cases from Ibadan had a bulkiness of lymph node (Williams et al, 1987) and extranodal involvement that appears more pronounced than those of cases from Japan and Jamaica, but similar to the observations of Fleming et al (1986) in another part of Nigeria. It is also possible that HTLV-I predisposes to high mortality early in life resulting in a loss to death of persons who otherwise would have developed ATL as adults, possibly through the causation of immunodeficiency as described in the HTLV-I associated paediatric syndrome of infective dermatitis (LeGrenade et al, 1990).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The clinical features of ATL in Nigeria differed from those described in other endemic areas. For example, the cases from Ibadan had a bulkiness of lymph node (Williams et al, 1987) and extranodal involvement that appears more pronounced than those of cases from Japan and Jamaica, but similar to the observations of Fleming et al (1986) in another part of Nigeria. It is also possible that HTLV-I predisposes to high mortality early in life resulting in a loss to death of persons who otherwise would have developed ATL as adults, possibly through the causation of immunodeficiency as described in the HTLV-I associated paediatric syndrome of infective dermatitis (LeGrenade et al, 1990).…”
Section: Discussionsupporting
confidence: 72%
“…In Trinidad/Tobago, HTLV-I infection is restricted largely to persons of African ancestry despite the fact that the population is equally divided between persons of Asian and African origin supporting the concept that the virus is endemic in Africa (Bartholomew et al, 1985). This hypothesis was supported by our previous case report of a Nigerian with classical adult T-cell leukaemia/lymphoma (Williams et al, 1984) and recent population surveys of HTLV-I in various locales of Africa (Fleming et al, 1982;Saxinger et al, 1984;Fleming et al, 1986;Williams et al, 1987). While the validity of the early HTLV-I serology in Africa has been questioned (Weiss et al, 1986) especially because of the remarkable discrepancy between the enzyme-linked screening and confirmatory assays when compared with the more sensitive Western immunoblot assay (Constantine et al, 1988;CDC, MMWR, 1988) .…”
supporting
confidence: 57%
“…Currently, routine screening of blood donors for HTLV I/II is not practiced in Nigeria. Different studies carried out in Nigeria showed varied prevalence rates for HTLV I among blood donors in Nigeria [11][12][13][14][15][16]. Prevalence rates among blood donors in in Lagos ranged from 0.7% in Lagos [17].…”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 mainly infects inhabitants of southern Japan 16,41 , equatorial Africa 8 , Malasia 50 , the Caribbean 6 , South America (Brazil 34 , Colombia 51 , Peru 19 , Chile 44 , Argentina 14 , and Uruguay 28 ), and the southern United States 5,46 . In Brazil, since the introduction of HTLV-1 screening tests in blood centers, the virus has been found among blood donors with a prevalence varying from state to state.…”
Section: Introductionmentioning
confidence: 99%